Opposite Impacts of Interannual and Decadal Pacific Variability in the Extratropics. Issue 2 (23rd January 2023) - Seabrook, M.; Smith, D. M.; Dunstone, N. J.; Eade, R.; Hermanson, L.; Scaife, A. A.; Hardiman, S. C.
Abstract: It is well established that the positive phase of El Niño Southern Oscillation (ENSO) tends to weaken the Northern Hemisphere stratospheric polar vortex (SPV), promoting a negative North Atlantic Oscillation (NAO). Pacific Decadal Variability (PDV) is characterized by a pattern of sea surface temperatures similar to ENSO, but its impacts are more uncertain: some studies suggest similar impacts of ENSO and PDV on the SPV and NAO, while others find the opposite. We use climate model experiments and reanalysis to find further evidence supporting opposite interannual and decadal impacts of Pacific variability on the extratropics. We propose that the decadal strengthening of the SPV in response to positive PDV is caused by a build‐up of stratospheric water vapor leading to enhanced cooling at the poles, an increased meridional temperature gradient and a strengthened extratropical jet. Our results are important for understanding decadal variability, seasonal to decadal forecasts and climate projections. Plain Language Summary: El Niño Southern Oscillation (ENSO) dominates the year‐to‐year variability in the Pacific and is crucial for seasonal forecasts, whereas Pacific Decadal Variability (PDV) describes changes which are important in decadal predictions. The impacts of ENSO have been well studied but the impacts of PDV are more uncertain despite the pattern of sea surface temperature being very similar to ENSO. In this study we use observational reanalysis and climate models to show that positive PDV and ENSO phases have opposite impacts on stratospheric winds. We argue that this is because a positive PDV allows more water vapor to enter the stratosphere which builds up over the period of a decade. This causes a cooling over the Northern Hemisphere polar stratosphere and hence a strengthening of Northern Hemisphere polar stratospheric winds, resulting in different surface impacts. This result is important for understanding climate variability and improving climate predictions and projections. Key Points: Positive phases of pacific variability weaken the stratospheric polar vortex on interannual timescales but strengthen it on a decadal basis We hypothesize this is due to a long‐term build‐up of stratospheric water, due to an increase of tropical tropopause temperatures Impacts of Pacific variability on north Atlantic winter sea level pressure are also different on interannual and decadal timescales